ILMU PENGETAHUAN DAN PERKEMBANGANNYA: Tantangan Kemajuan dan Kemunduran Dunia Muslim - Hasyim, Farid (ULUL ALBAB Jurnal Studi Islam, 2012)
Many history of science writers thought that nowadays science phenomenon achieved by the West without including contribution of some other Moslem countries science. They truly interested with these believed, since the fact that science revolution happen in West Europe. However, labelling all aspect of science invention on the West precisely uncorrect. The fact that some other nation and civilization, such as Greece, China and India strongly and spreadly constribute, direct and indirectly to these science phenomenon. Among nations and itâ€™s contribution to improvement of science which should be countable; is Muslim civilitation with itâ€™s Islam civilitation. Importance of their contribution so that someone surely believed that if Muslim science would be the only trigger of science revolution on the West. Someone also logically believe that revolution of science could be happen among Muslim if only some events would not be happen since it sparge the science development at that time. Â